Analisis Aspek Feminisme Radikal dalam Cerpen Anjing Kampus Karya Lia Laeli Muniroh - Putik Hatul Janah; Jihan Noor A’isah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this study is to describe the short story Anjing Kampus by Lia Laeli Munaroh as seen through the perspective of feminism. This research is a qualitative descriptive research. The object of this research is the short story Anjing Kampus by Lia Laeli Muniroh published in Ruang Sastra in 2023, with data sources in the form of quotations and in the form of words, phrases, clauses, sentences, and paragraphs that show aspects of radical feminism in the short story Anjing Kampus by Lia Laeli Muniroh. The results of the research analysis can be seen in terms of radical feminism, the role of the main character